Numerical Simulation for Dual Solid Particle Separation Using Fluidized Bed - Muhammad Lutfil Amin; Nur Ikhwan (Engineering Proceedings)
Particle separation is a common process in various industries, particularly in mineral processing. Therefore, this research aimed to evaluate the performance of separation method using fluidized bed. The evaluation was performed using silica gel particle with diameters of 0.9 and 3 mm, including diesel fuel as fuel. This simulation was carried out to obtain the optimum separation of small-sized particle (0.9 mm) based on variations in fluid velocity (0.034, 0.068, and 0.102 m/s), outlet height (0.3, 0.6, and 0.9 m), and time. Optimum separation, defined by maximum separation efficiency (99%) in minimum time for separation, was determined using Computational Particle Fluid Dynamics software (CPFD VR 17.4.0). Separation efficiency of simulation results was validated by experimental research The results showed that, at velocity of 0.034 m/s, big particle could be partially separated at an outlet height of 0.9 m. At velocity of 0.068 m/s, small particle was separated at an outlet height of 0.6 m for 220 s, and big particle at 0.9, with a time longer than 300 s. Based on these results, optimum condition was obtained at velocity of 0.102 m/s, where small and big particle was separated at a time of 100 s, with output heights of 0.9 and 0.6 m, respectively.